Mathematical modeling of sound insulation for sound suppressing lightweight structured panels (SSLWSP) - L. Murzinov, v; V. Murzinov, p; V. Murzinov, Yu; I. Buyanov, V; A. Popov, V (International Journal of Engineering and Technology, 2018)
The article presents SSLWSP panels, the feature of which is a small weight and good soundproofing properties. The article acquired the model of sound insulation for SSLWSP panels. The modeling of sound insulation is based on the sound-permeability model of thin iso-tropic sheet material, from which SSLWSP panels are made. An experimental verification of the obtained sound insulation model showed the convergence of experimental and theoretical values. The best convergence of theoretical and experimental data falls on the frequencies corresponding to a speech range.